T2 Relaxometry Evidence of Microstructural Changes in Diffusely Abnormal White Matter in Relapsing–Remitting Multiple Sclerosis and Clinically Isolated Syndrome: Impact on Visuomotor Performance. Issue 4 (6th May 2021) - Papadaki, Efrosini; Mastorodemos, Vasileios; Panou, Theodora; Pouli, Styliani; Spyridaki, Eirini; Kavroulakis, Eleftherios; Kalaitzakis, Georgios; Maris, Thomas G.; Simos, Panagiotis
Abstract : Background: Although diffusely abnormal white matter (DAWM) is commonly seen in multiple sclerosis (MS), it is rarely considered in clinical/imaging studies. Purpose: To evaluate quantitative markers of microstructural changes in DAWM of patients with clinically isolated syndrome (CIS) and relapsing–remitting MS (RR‐MS) in relation to MS lesions and degree of neurocognitive impairment, by using a multi‐echo spin echo (MESE) Proton Density PD‐to‐T2 sequence. Study Type: Prospective, cross‐sectional. Population: Thirty‐seven RR‐MS patients, 33 CIS patients, and 52 healthy controls. Field Strength/Sequence: 1.5 T/T1‐, T2‐weighted, fluid‐attenuated inversion recovery, and MESE sequences. Assessment: Long T2, short T2, and myelin water fraction (MWF) values were estimated as indices of intra/extracellular water content and myelin content, respectively, in DAWM, posterior periventricular normal appearing white matter (NAWM), and focal MS lesions, classified according to their signal intensity on T1 sequences. Patients were, also, administered a battery of neuropsychological tests. Statistical Tests: Comparisons of T2 and MWF values in DAWM, NAWM, and MS lesions were examined, using two‐way mixed analyses of variance. Associations of Grooved Pegboard performance with T2 and MWF values in DAWM and NAWM were assessed using Pearson correlation coefficients. Results: T2 and MWF values of DAWM were intermediate between the respective values of NAWM and T1 hypointense focal lesions, while there was no difference between the respective values of DAWM and T1‐isointense lesions. T2 values in DAWM were strongly associated with visuomotor performance in CIS patients. Data Conclusion: Intra/extracellular water and myelin water content of DAWM are similar to those of T1‐isointense lesions and predict visuomotor performance in CIS patients. Level of Evidence: 2 Technical Efficacy: Stage 2